2018
DOI: 10.3389/fpls.2018.00587
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the Efficiency of Phenotyping Early Traits in a Greenhouse Automated Platform for Predicting Drought Tolerance of Soybean in the Field

Abstract: Conventional field phenotyping for drought tolerance, the most important factor limiting yield at a global scale, is labor-intensive and time-consuming. Automated greenhouse platforms can increase the precision and throughput of plant phenotyping and contribute to a faster release of drought tolerant varieties. The aim of this work was to establish a framework of analysis to identify early traits which could be efficiently measured in a greenhouse automated phenotyping platform, for predicting the drought tole… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(19 citation statements)
references
References 49 publications
0
19
0
Order By: Relevance
“…Similarly, Peirone et al . [ 77 ] found that transpiration efficiency measured in greenhouse conditions at the early stages of soybean growth was the most efficient trait in predicting drought tolerance in the field and Knoch et al . [ 75 ] showed that early plant growth of canola was a complex trait that involves several temporally dynamic loci with medium and small effects.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, Peirone et al . [ 77 ] found that transpiration efficiency measured in greenhouse conditions at the early stages of soybean growth was the most efficient trait in predicting drought tolerance in the field and Knoch et al . [ 75 ] showed that early plant growth of canola was a complex trait that involves several temporally dynamic loci with medium and small effects.…”
Section: Resultsmentioning
confidence: 99%
“…In the end, the paper was focused on QTL associated with transpiration efficiency [24]. Similarly, Peirone et al [77] found that transpiration efficiency measured in greenhouse conditions at the early stages of soybean growth was the most efficient trait in predicting drought tolerance in the field and Knoch et al [75] showed that early plant growth of canola was a complex trait that involves several temporally dynamic loci with medium and small effects. Furthermore, the heritabilities of TPA-measured traits were relatively low in our experiments, ranging between 0.5 and 0.6 (S6 Table), and these values were based on spatially adjusted means.…”
Section: Plos Onementioning
confidence: 99%
“…Associations between greenhouse and field trials using the same varieties is further complicated by other environmental factors such as soil type, microorganisms, N and water availability (Cormier et al, 2016; Nguyen et al, 2017). However, several studies have reported a causal relationship between greenhouse screens and the field performance of crops (Chapuis et al, 2012; Pardo et al, 2015; Peirone et al, 2018). Therefore, results from vegetative screens in greenhouses, like those in the current study, can still be useful indicators of the performance of genotypes for NUE, which can help reduce the time and cost of developing new breeding materials.…”
Section: Discussionmentioning
confidence: 99%
“…Greenhouse experiments provide a controlled, stable environment and reproducible evaluations, but are limited in the size of plots that can be used for evaluation. On the other hand, field experiments reflect ‘real-world’ responses under water deficit stress, but these can also be affected by complicated environmental factors [20]. Given consideration of the environmental difference, both greenhouse and field phenotypic data were collected for QTL analysis in this study, which could enable us to detect drought response QTL in various environments.…”
Section: Discussionmentioning
confidence: 99%